Applicability and relevance of models that predict short term outcome after intracerebral haemorrhage. Issue 6 (16th May 2005) - Ariesen, M J; Algra, A; van der Worp, H B; Rinkel, G J E
Abstract : Objectives: Several models for prediction of short term outcome after intracerebral haemorrhage (ICH) have been published, however, these are rarely used in clinical practice for treatment decisions. This study was conducted to identify current models for prediction of short term outcome after ICH and to evaluate their clinical applicability and relevance in treatment decisions. Methods: MEDLINE was searched from 1966 to June 2003 and studies were included if they met predefined criteria. Regression coefficients of multivariate models were extracted. Two neurologists independently evaluated the models for applicability in clinical practice. To assess clinical relevance and accuracy of each model, in a validation series of 122 patients the proportion with a ⩾95% probability of death or poor outcome and the actual 30 day case fatality in these patients were calculated. Receiver operator characteristic (ROC) curves were computed for assessment of discriminatory power. Results: A total of 18 prognostic models were identified, of which 14 appeared easy to apply. In the validation series, the proportion of patients with a ⩾95% probability of death or poor outcome ranged from 0% to 43% (median 23%). The 30 day case fatality in these patients ranged from 75% to 100% (median 93%). The area under the ROC curves ranged from 0.81 to 0.90. Conclusions: Most models are easy to apply and can generate a high probability of death or poor outcome. However, only a small proportion of patients have such a high probability, and 30 day case fatality is not always correctly predicted. Therefore, current models have limited relevance in triage, but can be used to estimate the chances of survival of individual patients.